Sexual abuse and self- reconstruction: psychosocial study of Dorothy Allison’s ''Bastard out of Carolina'' and Edmund White’s ''A boy’s own story'' - SHAFIQ, J.A. (Utopía y Praxis Latinoamericana, 2021)
ABSTRACT Increasingly, there is more interest in studying the perverted sexual relationship; and their causes and effects. The social and psychological impact of such relationships should not be overlooked. Writers who write about such topics are usually inspired by personal experiences; the semi-autobiographical element is usually present in such works, whether Lesbian or gay, the novelist uses his story as a kind of thereby or catharsis in an attempt to seek equilibrium. In her novel Bastard Out of Carolina, Dorothy Allison tells a story of a girl who represents the novelist herself. RESUMEN Cada vez hay más interés en estudiar la relación sexual pervertida; y sus causas y efectos. El impacto social y psicológico de tales relaciones no debe pasarse por alto. Los escritores que escriben sobre estos temas suelen inspirarse en experiencias personales; el elemento semi-autobiográfico suele estar presente en tales obras, ya sea lesbiana o gay, el novelista usa su historia como una especie de tal o catarsis en un intento de buscar el equilibrio. En su novela Bastard Out of Carolina, Dorothy Allison cuenta la historia de una niña que representa a la novelista.